Biotechnological Plastic Degradation and Valorization Using Systems Metabolic Engineering - Lee Ga hyun; Kim Do Wook; JIN YUN HUI; Kim, Sang Min; Lim, Eui Seok; Cha Minji; Ko, Ja Kyong; Gong, Gyeong taek; Lee, Sun-Mi; Um, Young soon; Han, Sung Ok; Ahn, Jung Ho (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Various kinds of plastics have been developed over the past century, vastly improving the quality of life. However, the indiscriminate production and irresponsible management of plastics have led to the accumulation of plastic waste, emerging as a pressing environmental concern. To establish a clean and sustainable plastic economy, plastic recycling becomes imperative to mitigate resource depletion and replace non-eco-friendly processes, such as incineration. Although chemical and mechanical recycling technologies exist, the prevalence of composite plastics in product manufacturing complicates recycling efforts. In recent years, the biodegradation of plastics using enzymes and microorganisms has been reported, opening a new possibility for biotechnological plastic degradation and bio-upcycling. This review provides an overview of microbial strains capable of degrading various plastics, highlighting key enzymes and their role. In addition, recent advances in plastic waste valorization technology based on systems metabolic engineering are explored in detail. Finally, future perspectives on systems metabolic engineering strategies to develop a circular plastic bioeconomy are discussed.